Syariah Courts in Malaysia and the Development of Islamic Jurisprudence: The Study of Istihsan - Mohd Hafiz Jamaludin; Ahmad Hidayat Buang (International Journal of Nusantara Islam, 2013)
Malaysia is among the countries, which have very close relations with Shafi'i madhhab in term of Islamic Law. This can be seen from the provisions of Syariah Law in Malaysia where the opinion of the Shafi'i madhhab is preferred than other madhhabs. However, the current situations and issues cause that the other opinions from the other madhhabs are also used and practiced in order to provide the best solutions. This is also true in respect on the use of sources of Islamic law, such as Istihsan, Istislah and Qawl Sahabi, which are rejected by the Shafi'i madhhab. Therefore, this study attempts to analyze the development of Islamic law, particularly in the application of the concept of Istihsan in the Syariah Courts in Malaysia. This study has examined a number of cases reported in the Jurnal Hukum issued by the Syariah Judiciary Department of Malaysia (JKSM). The result of this study found that in several cases, the judges have applied indirectly the concept of Istihsan in their judgment. It is also found that it is actually the provisions of the law that allows the Shariah judges to indirectly apply this concept.